Business management in fisheries and aquaculture - Chaston, Ian (Fishing News Books, 1984)
This text is designed for the practising manager who wishes to upgrade his knowlege of modern management methods and for the public sector advisor who typically has a scientific background. Because it can be used as the basis for a college level introductory syllabus on commercial management in the industry, it is also suitable reading for the manager with no formal management training. The book's objective is to describe the concept of strategic management where future plans are based upon a detailed analyis of a company's strengths and weaknesses relative to the business environment. To execute a business strategy requires finance, marketing, production and personnel management. These skills are carefully introduced by presenting them in the context of actual examples drawn from fisheries and aquaculture.